Ethnobotanical knowledge and its role in biodiversity conservation of Tatar Sunda, Indonesia - LESY LUZYAWATI; IDAH HAMIDAH; LUTHFIYATI NURAFIFAH (Society for Indonesian Biodiversity, 2026)
Abstract. Luzyawati L, Hamidah I, Nurafifah L. 2026. Ethnobotanical knowledge and its role in biodiversity conservation of Tatar Sunda, Indonesia. Biodiversitas 27 (2): d270218. https://doi.org/10.13057/biodiv/d270218. Tatar Sunda in Indonesia is an area distinguished by its exceptional biodiversity and enduring cultural heritage. However, this vital biocultural knowledge faces significant threats from modernization and the erosion of intergenerational transmission. To ensure effective biodiversity conservation, it is necessary to integrate biophysical, socio-economic, and cultural dimensions, specifically ethnobotanical knowledge. Therefore, this study aims to document the integration of biodiversity and indigenous ethnobotanical knowledge of Tatar Sunda community, focusing on medicinal and timber plant species and their conservation significance. This study was conducted in five representative communities across West Java and Banten Provinces in Indonesia selected to capture diverse ecological and cultural settings. A mixed-method ethnobiological approach combining qualitative ethnography and quantitative ethnobotanical indices (SUV, FUV, ICF, and FL) was employed. This approach was carried out through observation, semi-structured interviews with 120 local experts, and field documentation. A total of 83 medicinal plant species and 46 timber species were documented. Quantitative analysis revealed strong communal consensus for 23 disease categories and highlighted the high cultural importance of key families, notably Zingiberaceae (medicinal) and Fabaceae (timber). Species from Poaceae family were widely used by the community for both medicinal and timber purposes. Crucially, indigenous conservation practices, such as sacred forest protection (hutan larangan), restricted harvesting, and cultural taboos (pamali), were found to be crucial for maintaining ecological balance. This study provides a comprehensive baseline, confirming that TEK in Sundanese community is not a relic but a vital, sustainable strategy for biodiversity conservation.